2015
DOI: 10.1007/s00262-015-1715-3
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study of adjuvant immunotherapy with sentinel lymph node T lymphocytes in patients with colorectal cancer

Abstract: Although the development of multi-disciplinary management has improved the survival of colorectal cancer (CRC), the prognosis of metastatic CRC patients remains poor. Accumulating evidence has demonstrated that immunotherapy with cancer vaccines and adoptive T cell transfusions may improve outcomes as an adjuvant to current standard CRC treatment. In this phase I/II study, 71 CRC patients who underwent radical surgery (stage I–III, n = 46) or palliative surgery (stage IV with non-resectable synchronous metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 46 publications
0
39
0
Order By: Relevance
“…Another ACT trial involving sentinel lymph node (SLN)-T cells instead of TILs was conducted in 16 and 55 CRC patients included in a pilot study and a phase I/II clinical trial, respectively. Encouragingly, 4 complete responses, 1 partial response and 4 cases of stable disease were observed in the 9 patients with stage IV CRC in each study (185,186). Other studies in CRC are currently ongoing (NCT03935893, NCT01174121, and NCT03904537) to confirm these preliminary results which suggest that ACT with TILs or SLN-T cells could benefit CRC patients, but also highlight a need for improvement of these therapies.…”
Section: Adoptive T-cell Therapy In Crcmentioning
confidence: 78%
“…Another ACT trial involving sentinel lymph node (SLN)-T cells instead of TILs was conducted in 16 and 55 CRC patients included in a pilot study and a phase I/II clinical trial, respectively. Encouragingly, 4 complete responses, 1 partial response and 4 cases of stable disease were observed in the 9 patients with stage IV CRC in each study (185,186). Other studies in CRC are currently ongoing (NCT03935893, NCT01174121, and NCT03904537) to confirm these preliminary results which suggest that ACT with TILs or SLN-T cells could benefit CRC patients, but also highlight a need for improvement of these therapies.…”
Section: Adoptive T-cell Therapy In Crcmentioning
confidence: 78%
“…[9][10][11] Some investigators have used TDLNs as a source of T cells for adoptive T cell therapy and demonstrated their anti-tumor activity in clinical trials. 12,13 However, T cell repertoires in TDLNs have not been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the procedure was reproducible as complete repeats of the stimulation procedures under research and under full GMP conditions showed similar results when compared to the first runs. Promising results already have been obtained in a pilot study in colorectal cancer patients, as immunotherapy or in adjuvant setting, using TDLN-expanded T cells for ACT [33, 34]. …”
Section: Discussionmentioning
confidence: 99%